2011
DOI: 10.1007/s00586-011-1762-1
|View full text |Cite
|
Sign up to set email alerts
|

A minimally invasive posterior lumbar interbody fusion for degenerative lumbar spine instabilities

Abstract: Percutaneous techniques may be helpful to reduce approach-related morbidity of conventional open surgery. The aim of the study was to evaluate the feasibility and safety of mini-open posterior lumbar interbody fusion for instabilities and degenerative disc diseases. From

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
3
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 11 publications
4
21
3
8
Order By: Relevance
“…Many authors have reported excellent clinical outcomes as well as high fusion rates after PLIF [10,11], indicating that PLIF is an appropriate procedure for treating an abnormal mobile segment. Although transforaminal lumbar interbody fusion (TLIF) is also reported to produce high fusion rate and excellent clinical outcomes [18,19], the additional fusion needs enough rigidity because of more stress by the longer lever arm. PLIF has more advantage in achieving solid fusion by removing intervertebral material and cartilaginous endplates through bilateral wide annulotomy and harvesting more amount of local autograft.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have reported excellent clinical outcomes as well as high fusion rates after PLIF [10,11], indicating that PLIF is an appropriate procedure for treating an abnormal mobile segment. Although transforaminal lumbar interbody fusion (TLIF) is also reported to produce high fusion rate and excellent clinical outcomes [18,19], the additional fusion needs enough rigidity because of more stress by the longer lever arm. PLIF has more advantage in achieving solid fusion by removing intervertebral material and cartilaginous endplates through bilateral wide annulotomy and harvesting more amount of local autograft.…”
Section: Discussionmentioning
confidence: 99%
“…However, the approach-related morbidity, that results from iatrogenic soft-tissue injury, which includes paraspinal muscle injury, has become a major problem [1,2]. Several procedures, including minimally invasive techniques, have been developed as potential solutions to this problem [3][4][5][6]. Lumbar spinous process-splitting laminectomy, in which the muscular attachment is left intact, has been reported to decrease the degree of postoperative paraspinal muscular atrophy [7].…”
Section: Introductionmentioning
confidence: 99%
“…Because of a reduced destruction of the soft tissues, proponents of these MIS techniques claim to achieve superior clinical results with reduced postoperative pain, narcotic use, and hospital length of stay [4,5,10,12,16,23]. On the other hand, performing percutaneous instrumentation, fusion and decompression in complex cases with severe arthritic and stenotic changes could increase the complication rate and lower the accuracy of pedicle screw insertion [6].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it has been suggested that the procedure should be tailored to each patient depending on imaging findings and symptoms-for example, ventral approaches in cases of high-grade spondylolisthesis or unilateral approaches in cases of unilateral symptoms [2,29]. The authors of previous studies of MIS and especially MIS-TLIF have commonly neglected the heterogeneity of the patient population by including such complex cases in the patient population without differentiating the efficacy of the surgery on these patients [5,12,18,20,23,26]. Other authors either a priori excluded such complex cases from performing MIS techniques or recommended that MIS should be performed at the discretion of the surgeon [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation